Orthoquinone and Naphthalenone Derivatives from Berrya ammonilla and Their Anti-Inflammatory Activity - Chou, Tsung-Hsien; Chien, Sheng-Kan; Hwang, Tsong-Long; Wei, Dau-Chang; Chen, Ih-Sheng; Sung, Ping-Jyun; Cheng, Ming-Jen; Yang, Sheng-Zehn; Chang, Ken-Ming; Chen, Jih-Jung (Planta Medica, 2012)
A new orthoquinone, berryammone A (1), and four new naphthalenone derivatives, berryammone B (2), berryammone C (3), 6-O-methylberryammone C (4), and 4-O-methylberryammone C (5), have been isolated from the stem of Berrya ammonilla, together with eleven known compounds (6–16). The structures of these new compounds were determined through spectroscopic and MS analyses. Among the isolates, compounds 1–3, 5, (+)-pinoresinol (6), and betulinic acid (12) exhibited inhibition (IC50 ≤ 4.41 µM) of superoxide anion generation by human neutrophils in response to formyl-L-methionyl-L-leucyl-L-phenylalanine/cytochalasin B (fMLP/CB). Compounds 1, 2, and 5 also inhibited fMLP/CB-induced elastase release with IC50 values ≤ 3.95 µM.
Keywords: Berrya ammonilla; Tiliaceae; orthoquinone; naphthalenone; anti-inflammatory activity